Ethnic identity and immigrant homeownership - Amelie F. Constant; Rowan Roberts; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Immigrants are much less likely to own their homes than natives, even after controlling for a broad range of life-cycle and socio-economic characteristics and housing market conditions. This paper extends the analysis of immigrant housing tenure choice by explicitly accounting for ethnic identity as a potential influence on the homeownership decision, using a two-dimensional model of ethnic identity that incorporates attachments to both origin and host cultures. The evidence suggests that immigrants with a stronger commitment to the host country are more likely to achieve homeownership for a given set of socioeconomic and demographic characteristics, regardless of their level of attachment to their home country.
Keywords: R21; F22; J15; Z10; 330; ethnicity; ethnic identity; immigration; immigrant integration; homeownership; Migranten; Ethnische Gruppe; Kulturpsychologie; Tenure Choice; Deutschland